Short-term co-ingestion of creatine and sodium bicarbonate improves anaerobic performance in trained taekwondo athletes - Amir Sarshin; Vahid Fallahi; Scott C. Forbes; Alireza Rahimi; Majid S. Koozehchian; Darren G. Candow; Mojtaba Kaviani; Seyed Nemat khalifeh; Vahid Abdollahi; Alireza Naderi (Taylor & Francis Group, 2021)
Background Creatine (CR) and sodium bicarbonate (SB) alone improve anaerobic performance. However, the ergogenic effects of CR and SB co-ingestion on taekwondo anaerobic performance remains unknown. Methods Forty trained taekwondo athletes (21 ± 1 y.; 180.5 ± 7.3 cm; 72.7 ± 8.6 kg) were randomized to: (i) CR and SB (CR + SB; 20 g of CR+ 0.5 g·kg− 1·d− 1 of SB), (ii) CR, (iii) SB, (iv) placebo (PLA), or (v) control (CON) for 5 days. Before and after supplementation, participants completed 3 bouts of a Taekwondo Anaerobic Intermittent Kick Test (TAIKT) to determine changes in peak power (PP), mean power (MP), and fatigue index (FI). Blood lactate (BL) was measured before, immediately following, and 3 min post-TAIKT. Results PP and MP increased over time (P < 0.05) following CR + SB, CR, and SB ingestion, with no changes in the PLA or CON groups. There was a greater increase over time in MP following CR + SB (Absolute Δ: 1.15 ± 0.28 W∙kg67) compared to CR (Absolute Δ: 0.43 ± 0.33 W∙kg67; P < 0.001) and SB (Absolute Δ: 0.73 ± 0.24 W∙kg67; P = 0.03). There were no significant time and condition effect for FI (P > 0.05). BL increased following exercise across all groups; however, CR + SB and SB post-exercise BL was lower compared to CR, PLA, and CON (P < 0.05). Conclusion Short-term CR and SB alone enhance TAIKT performance in trained taekwondo athletes. Co-ingestion of CR and SB augments MP compared to CR and SB alone, with similar PP improvements.